Computational intelligence in music, sound, art and design : 6th International Conference, EvoMUSART 2017, Amsterdam, the Netherlands, April 19-21, 2017, Proceedings /: 6th International Conference, EvoMUSART 2017, Amsterdam, the Netherlands, April 19-21, 2017, Proceedings. (2017) - Unknown
No abstract available